Luteinizing hormone-induced Akt phosphorylation and androgen production are modulated by MAP Kinase in bovine theca cells - Fukuda Shin; Orisaka Makoto; Tajima Kimihisa; Hattori Katsushige; Kotsuji Fumikazu (BMC, 2009)
Abstract Background Theca cells play an important role in controlling ovarian steroidogenesis by providing aromatizable androgens for granulosa cell estrogen biosynthesis. Although it is well established that the steroidogenic activity of theca cells is mainly regulated by LH, the intracellular signal transduction mechanisms that regulate thecal proliferation and/or steroidogenesis remain obscure. In this study, we examined whether and how LH controls the PI3K/Akt signaling pathway and androgen production in bovine theca cells. We also explored whether this LH-induced PI3K/Akt activation is modulated with other signaling pathways (i.e. PKA and MAPK). Methods Ovarian theca cells were isolated from bovine small antral follicles and were incubated with LH for various durations. Phospho-Akt and total-Akt content in the cultured theca cells were examined using Western blotting. Androstenedione levels in the spent media were determined using EIA. Semi-quantitative RT-PCR analyses were conducted to analyze the mRNA levels of CYP17A1 and StAR in the theca cells. To examine whether Akt activity is involved in theca cell androgen production, the PI3K inhibitors wortmannin and LY294002 were also added to the cells. Results Akt is constitutively expressed, but is gradually phosphorylated in cultured bovine theca cells through exposure to LH. LH significantly increased androstenedione production in bovine theca cells, whereas addition of the wortmannin and LY294002 significantly decreased LH-induced androstenedione production. LH significantly increased CYP17A1 mRNA level in theca cells, whereas addition of LY294002 significantly decreased LH-induced CYP17A1 expression. Neither LH nor PI3K inhibitors alter the mRNA levels of StAR in theca cells. Although H89 (a selective inhibitor of PKA) does not affect LH-mediated changes in Akt, U0126 (a potent MEK inhibitor) suppressed LH-induced Akt phosphorylation, CYP17A1 expression, and androgen production in theca cells. Conclusion These results indicate that LH stimulates CYP17 mRNA expression and androgen production in theca cells via activation of the PI3K/Akt pathway. The LH-induced Akt phosphorylation and androgen production are modulated by the MAPK signaling in bovine theca cells.